Validity and reliability of the lederman Prenatal Self-Evaluation Questionnaire (PSEQ) in Brazil - Janiny Lima e Silva; Matheus de Sousa Mata; Saionara Maria Aires Câmara; Íris do Céu Clara Costa; Kleyton Santos de Medeiros; Ricardo Ney Cobucci; Ana Katherine Gonçalves (BMC, 2021)
Abstract Background The Lederman Prenatal Self-Evaluation Questionnaire (PSEQ) is used to assess psychosocial adaptation to pregnancy, labor, childbirth, and maternity. The PSEQ is a tool used in various countries and has been translated into Portuguese; however, it needs to be validated in Brazil. This study aimed to analyze the validity and reliability of the PSEQ in Brazilian pregnant women. Method This methodological validity study investigated internal consistency and reliability using Cronbach's alpha and intraclass correlation coefficients. Construct validity was assessed using Pearson's correlation between domains and confirmatory factor analysis. To assess concurrent validity, Pearson's correlation between the different domains of the PSEQ and Prenatal Psychosocial Profile-Portuguese Version (PPP-VP) was determined. The level of significance was set at 5%. Results This study included 399 pregnant women in the northeastern region of Brazil. The internal consistency and reliability of the total PSEQ score were high (Cronbach's alpha = 0.89; intraclass correlation coefficient = 0.95). Validity analysis showed positive and significant correlations between all PSEQ domains, ranging from 0.14 to 0.56. Confirmatory factor analysis demonstrated the following values of goodness of fit: RMSEA = 0.05, SRMR = 0.08, CFI = 0.61, χ2/df = 1.77. The discriminant and concurrent validities of the PSEQ were confirmed. Conclusions The Portuguese version of the PSEQ has adequate psychometric properties and is a valid and reliable tool to evaluate psychosocial adaptation to pregnancy in Brazilian pregnant women.